(untitled) (LSP International Journal, 2021)
English has been regarded as one of the core subjects in the Malaysian Certificate of Education or known as the Sijil Pelajaran Malaysia (SPM). There has been a concern over the writing components in English language papers at the SPM level. Writing requires students’ competence in syntax, coherence, developing and arranging ideas, mechanics in writing and appropriate use of vocabulary. A concern over students who produce very limited number of words in their essays has resulted in the lack of content to be assessed which then led to low scores. This paper presents an error analysis focusing on the types of errors found in students’ written test scripts to identify the weaknesses of students' writing abilities. The study adopts a qualitative approach where the students’ written assessment texts were collected. A total of 18 upper secondary Year Four students (aged 16 years old) were selected as the research participants. The selection of participants was carried out in a secondary school in one of the states in Malaysia. The students’ written tests were analysed to identify the emerging categories of language use, focusing on language and grammar inaccuracies. It is found that students have the idea on how to write the answers to the task but seem to have difficulties putting the ideas in the correct structure.